2021
DOI: 10.1073/pnas.2017435118
|View full text |Cite
|
Sign up to set email alerts
|

Membrane bending by protein phase separation

Abstract: Membrane bending is a ubiquitous cellular process that is required for membrane traffic, cell motility, organelle biogenesis, and cell division. Proteins that bind to membranes using specific structural features, such as wedge-like amphipathic helices and crescent-shaped scaffolds, are thought to be the primary drivers of membrane bending. However, many membrane-binding proteins have substantial regions of intrinsic disorder which lack a stable three-dimensional structure. Interestingly, many of these disorder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
172
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 66 publications
18
172
0
Order By: Relevance
“…However, one interesting observation in all the species we investigated here is that there was no clear distinctive molecular machine at the base of the membrane projections, raising the question of what drives their formation. This observation is consistent with a recent study which showed that liquid-like assemblies of proteins in membranes can lead to the formation of tubular extensions without the need for solid scaffolds [39].…”
Section: Discussionsupporting
confidence: 93%
“…However, one interesting observation in all the species we investigated here is that there was no clear distinctive molecular machine at the base of the membrane projections, raising the question of what drives their formation. This observation is consistent with a recent study which showed that liquid-like assemblies of proteins in membranes can lead to the formation of tubular extensions without the need for solid scaffolds [39].…”
Section: Discussionsupporting
confidence: 93%
“…We note that for a given value ofƜ, the variance decreases with increasingL for higher values ofƜ and this decrease is more dramatic when compared to the Cahn-Hilliard model (Figure 4b). Even though the number of patches remains more or less unaltered for small values ofƜ asL increases, the number decreases with increasingL for larger values ofƜ (Figure 7e), consistent with the stability behavior noted in Equation (52). These results suggest that the landscape of protein inhomogeneity is not only governed by theÂ-Ɯ space as is the case in the Cahn-Hilliard model; rather the curvature parameters, specificallyL in this case, can have a significant impact on the protein aggregation behavior.…”
Section: Numerical Simulationssupporting
confidence: 82%
“…These observations can lead to system-specific claims of whether membrane protein interactions result in a mechanochemical feedback between curvature and aggregation. In the context of specific biological processes such as endocytosis, aggregation of domains of protein-induced curvature is often assumed a priori or curvature is proposed as an organizing factor to explain cellular observations and experiments in reconstituted systems [46][47][48][49][50][51][52]. By developing a general theoretical framework that accounts for the coupled effects of protein diffusion, aggregation, and curvature generation, we have eliminated the need for such strong assumptions and more importantly, demonstrated that the intricate interactions between these different physics can lead to different regimes of pattern formation and membrane deformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin and mushroom spines, which have defined head shapes, require more mechanical features—heterogeneous force distributions, normal or axial forces, and an induced spontaneous deviatoric curvature representing the periodic protein rings or other deviatoric curvature inducing mechanics along the neck. The heterogeneous distribution of actin-mediated forces and BAR domain proteins can be related to the nanoscale organization of actin filaments and protein phase separation on the membrane surface (Nowak et al, 2021 ; Yuan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%